Provincial marine carbon sink transfer in China: structural drivers and key consumption pathways - Li, Yan; Deng, Cunfen; Jiang, Peng; Wei, Yigang; Wang, Ke (Frontiers in Marine Science, 2024)
The ocean is the largest carbon sink on Earth and an important pathway to China achieving carbon neutrality. From a consumption perspective, studying the capacity of marine carbon sink in each of China’s provinces and its inter-regional transfer is of great significance in harnessing the increase in ocean carbon sink driven by final demand. This article first calculates the production-side carbon sink in coastal provinces. Then, based on the 2007, 2012, 2015, and 2017 Chinese inter-regional input-output tables, each province's consumption-side marine carbon sink is calculated. The article further examines the influencing factors and key transfer paths for the growth of marine carbon sink through Structural Decomposition Analysis (SDA) and Structural Path Analysis (SPA) methods. The results show that each province’s total consumption-side carbon sink continues to rise, with significant regional disparities, demonstrating a trend of higher carbon sink in coastal provinces than inland provinces. Among the nine coastal provinces, Hainan and Guangdong are in a net input state regarding carbon sink transfer, while the other seven are in a net output state. SDA results indicate that the carbon sink intensity effect and the consumption demand effect are important factors inhibiting and promoting carbon sink growth, respectively, while the influence of the input-output technical effect is weak and variable. SPA analysis reveals that carbon sink outputs are primarily transferred to the food and tobacco sector, the agricultural and forestry products and services sector, and the wood processing and furniture industry. The key transfer paths mostly occur within a province, with a relatively small proportion of interprovincial transfer paths. Based on the research findings, this article suggests steadily increasing the proportion of marine product consumption, actively expanding the value chain of shellfish and seaweed industries, continuously strengthening coordination between land and marine industries, and further promoting the domestic circulation of marine carbon sinks.